Risk Analysis of Rice Farming in Polenga Village, Watubangga District, Kolaka Regency - Nurdiana Nurdiana; Nursalam Nursalam (Agribusiness Journal, 2021)
This study aims to determine the amount of production risk, cost risk and income risk of rice farmers in Polenga Village, Watubangga District, Kolaka Regency. The basic method used in this research is quantitative descriptive. Determination of the research sample using simple random sampling method, with a total sample of 48 rice farmers. The results of this study are the risks faced by farmers in Polenga Village, Kecamtan Watubangga, which is the production risk,  costs risk and  income risk. Based on the value of variation coefficients (CV) obtained, if CV 0.5 then the  production risk , costs and farm income borne by farmers is greater, while the value of CV ≤ 0.5, the farmer will always profit or break even. At the  production risk , the coefficient of variation (CV) was obtained at 0.1 ≤ 0.5 indicate that the farm  production risk  that burdened by farmers is low. Cost risk obtained by the value of the Coefficient of Variation (CV) of 0.2 ≤ 0.5 indicates that the farm cost risk  that burdened by farmers is low and the farm income risk is obtained a value of  Variation  Coefficient(CV) of 0.1 ≤ 0.5 indicates that burdened by farmers is low too.